The Impact of Collision Severity on Fatal Head Injuries in Road Traffic Accidents: A Postmortem Study - Ashish Kumar Singh; Sachin Kumar Tripathi; Rajiv Ratan Singh; Richa Choudhary; Pradeep Kumar Yadav (Journal of Forensic Science and Medicine)
Background: The increasing number of road traffic accidents (RTAs) worldwide is a major concern, posing a significant threat to people’s lives and well-being. Of particular worry is the substantial impact of fatal head injuries within the overall toll of these accidents. Understanding what contributes to head injuries in RTAs is complex, and specific factors such as the number of vehicles involved, speed, vehicle weight, and impact surface add layers of intricacy that need scrutiny. In simpler terms, we need to look at how these factors come into play. Aims and Objectives: The primary objective is to analyze the distribution of fatal head injury cases in RTAs, investigating how factors such as the number of vehicles, speed, vehicle weight, and impact surface influence the frequency and severity of such injuries. Materials and Methods: The study involves interviews with attendants of 604 RTA cases with head injuries, brought to the mortuary of S. R. N. Hospital at Moti Lal Nehru Medical College in Prayagraj. Ethical clearance and informed consent were secured before collecting preliminary data. Results: Significant findings indicate that fatal head injuries were most prevalent in two-vehicle accidents (53.15%), followed by multi-vehicle collisions (25.33%) and single-vehicle accidents involving pedestrians or objects (21.52%). Notably, the majority of impacts occurred on the front end (43.71%) and on main roads (52.98%), pinpointing specific areas for targeted road safety measures. In the subset of 604 fatal head injury cases from RTAs, comminuted skull fractures constituted 29.30%, while intact cranial fossa involvement was observed in 71.36%. Conclusion: Understanding the correlation between fatal head injuries and variables like the number of vehicles involved is pivotal for evidence-based interventions and policies. Collaboration among policymakers, safety experts, health-care providers, and researchers is imperative for reducing injuries and improving road safety. Identifying injury distribution causes informs traffic safety and medical response enhancements, contributing to a safer, healthier world through evidence-driven strategies.